LINKS BETWEEN THE CREATING SHARED VALUE CONCEPT AND A COMPANY’S MARKETING STRATEGY - Wojciech Grzegorczyk (Acta Scientiarum Polonorum. Oeconomia, 2021)
The aim of the article is to try to define the relationship between the corporate social responsibility (CSR) and the creating shared value (CSV) concepts and marketing strategy. To achieve this goal, a method of critical analysis of national and foreign literature relating to these issues was used. On this basis, conclusions were formulated defining the scope and content of these relations. They relate primarily to a company’s mission, marketing research and marketing strategy. The relationship between the CSV concept and marketing strategy can be particularly seen in the evaluation and selection of new geographic markets and new buyer segments. They refer to changes in product policy – creation of products constituting common value. Relationships also relate to distribution policy, which may include the creation of local clusters and the inclusion of companies from these markets in production and distribution.